Design Analysis and Space Layout in the Radiology Installation of Buleleng District Hospital - Ottu, Ayu Evelina; Wirajaya, I Wayan Angga; Dharmawan, I Bagus Gede; Mughnie, Burlian (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The Regional General Hospital of Buleleng Regency is a government-owned type B general hospital that has received full accreditation and serves as a teaching hospital in Bali. This study aims to analyze the design and layout of the Radiology Installation at RSUD Kabupaten Buleleng and evaluate the effectiveness of services and the implementation of Health and Safety (K3) for radiation workers. This research uses a descriptive qualitative method through direct observation, interviews with 10 respondents, and documentation. The results show that the Radiology Installation at RSUD Kabupaten Buleleng is divided into Central Radiology and Emergency Radiology, both of which face several challenges in service processes due to suboptimal design and layout, such as inefficient patient flow and non-ergonomic spaces. The implementation of Radiology K3 complies with current regulations. Several design and layout innovations have been proposed to the hospital management, but their implementation cannot be realized at this time.